2003
DOI: 10.1007/bf03040305
|View full text |Cite
|
Sign up to set email alerts
|

Are dyspeptic symptoms linked to Helicobacter pylori? A prospective cohort study among medical students

Abstract: Hp prevalence in Austrian medical students is similar to that in other western countries. There was no significant difference in Hp prevalence between dyspeptic students and asymptomatic students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
4
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
3
4
0
3
Order By: Relevance
“…Thus, the presence and the characteristics of symptoms/clinical conditions seem not to be sufficient to discriminate subjects infected with H. pylori. These results are in line with previous evidences documenting the lack of significant associations between H. pylori infection and gastrointestinal symptoms both in children with non-ulcer dyspepsia [31,32], and in adults [33,34]. As a consequence, as also suggested by the Working Group of the WHO IARC and considering the easy availability of noninvasive tests, it might be recommended that countries evaluate the possibility of introducing population-based H. pylori screening and treatment programs on the basis of a correct evaluation of local factors such as the disease burden and cost-effectiveness analysis [2].…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the presence and the characteristics of symptoms/clinical conditions seem not to be sufficient to discriminate subjects infected with H. pylori. These results are in line with previous evidences documenting the lack of significant associations between H. pylori infection and gastrointestinal symptoms both in children with non-ulcer dyspepsia [31,32], and in adults [33,34]. As a consequence, as also suggested by the Working Group of the WHO IARC and considering the easy availability of noninvasive tests, it might be recommended that countries evaluate the possibility of introducing population-based H. pylori screening and treatment programs on the basis of a correct evaluation of local factors such as the disease burden and cost-effectiveness analysis [2].…”
Section: Discussionsupporting
confidence: 93%
“…When H.pylori positivity was compared between people who had gastrointestinal problems in the last one month and who did not, it was found that the difference was not significant in the literature, in a study which analyzed H.pylori frequency and its relation with dyspeptic complains, there is no significant difference was detected in H.pylori positivity distributions and dyspeptic complains such as burning, bloating and sour taste in mouth were found (13,18,19), our study detected the same results of the literatures.…”
Section: Discussionmentioning
confidence: 97%
“…En los países en vías de desarrollo la prevalencia de infección por H. pylori es mayor en comparación con los países desarrollados, esta cifra oscila entre 10 y 60%, dependiendo de las condiciones, métodos diagnósticos y poblaciones estudiadas (16,20,21).…”
Section: Discussionunclassified
“…En estudiantes universitarios de países desarrollados se han reportado resultados contradictorios en la prevalencia de H. pylori, dando cifras mucho mayores (21,30) o por el contrario muy bajas (20,(31)(32)(33)(34) berse al tipo de población estudiada, ya que respecto a estudiantes del área de la salud existen datos muy similares, comunicando prevalencias de 25 hasta 38,6% (19,35,36). La elevada prevalencia mundial de infección por H. pylori, aunado a la insuficiente evidencia de sus rutas de contaminación, han dado lugar al estudio de diversos grupos sociales y de sus núcleos familiares ante la posibilidad de que esta sea la fuente de infección principal, adjudicando por lo tanto, al contacto estrecho entre sus miembros como una posible vía de contaminación; esto se ha hecho patente en algunos estudios realizados en niños y sus familias donde se ha encontrado esta asociación desde el punto de vista epidemiológico y molecular (4,10,16).…”
Section: Discussionunclassified
See 1 more Smart Citation